(untitled) (Journal of the College of Basic Education, 2024)
The study aims to clarify the meaning of creed, its importance and the depth of its impact on societies and human life, as belief in societies is the main engine for the acceleration of civilization development in it. The gods are the ones who inspire their minds in building civilization, and they are the ones who participate in war and triumph over their enemies. The contemporary civilized man now who has the correct belief sees the extent to which his society has been deeply affected by the creed and from its teachings, development and culture and reliance on the light of reason in building the civilized culture of his society, which is the course of his lofty evening. Looking to the reality of things, universes, existence and feeling to satisfy his mental, heart, and taste desires, in order to appreciate his place in this universe, and in this life.